2015
DOI: 10.1001/jamapediatrics.2015.2831
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Midpregnancy Glucose Levels and Risk of Congenital Heart Disease in Offspring

Abstract: IMPORTANCE There is a well-described association between maternal diabetes mellitus and risk of congenital heart disease (CHD) in offspring. Although the clinical diagnoses of type 2 diabetes or gestational diabetes are strong risk factors for CHD, subclinical abnormalities of glucose and insulin metabolism are common within the general population and could also confer risk for CHD. We hypothesize that continuous measures of blood analytes related to maternal diabetes are related to odds of cardiac malformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 26 publications
1
41
0
Order By: Relevance
“…It was recently reported that diabetes-induced elevation of maternal blood glucose levels during the 15th-18th week of gestation were correlated with CHD in a California-based case-control study (73). A mild but statistically significant increase in maternal serum glucose was associated with tetralogy of Fallot, a conotruncal heart defect, in offspring relative to unaffected controls, implying that subtle alterations in maternal glucose have the potential to serve as an environmental risk factor for CHD (73).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently reported that diabetes-induced elevation of maternal blood glucose levels during the 15th-18th week of gestation were correlated with CHD in a California-based case-control study (73). A mild but statistically significant increase in maternal serum glucose was associated with tetralogy of Fallot, a conotruncal heart defect, in offspring relative to unaffected controls, implying that subtle alterations in maternal glucose have the potential to serve as an environmental risk factor for CHD (73).…”
Section: Discussionmentioning
confidence: 99%
“…It was recently reported that diabetes-induced elevation of maternal blood glucose levels during the 15th-18th week of gestation were correlated with CHD in a California-based case-control study (73). A mild but statistically significant increase in maternal serum glucose was associated with tetralogy of Fallot, a conotruncal heart defect, in offspring relative to unaffected controls, implying that subtle alterations in maternal glucose have the potential to serve as an environmental risk factor for CHD (73). These findings, in combination with our work, suggest a gene-environment interaction model where increasing maternal glucose levels interact to reduce Notch1 expression levels to cause CHD, and this interaction is sensitized by genetic susceptibility loci, i.e., Notch1 haploinsufficiency, to cross a threshold for CHD occurrence ( Figure 7B).…”
Section: Discussionmentioning
confidence: 99%
“…Blood glucose levels in pregnant women in their first and second trimesters are associated with a risk of fetal malformation. [1][2][3] For example, fetal malformation rates were 0.8% (1/128) and 7.5% (22/292) in women with insulin-dependent diabetes with metabolic control before conception and after gestational week (GW) 8, respectively, compared to 1.4% in control women without diabetes. 1 Random second trimester blood glucose level is elevated in mothers of offspring with tetralogy of Fallot relative to controls (median 97 vs 91.5 mg/dL).…”
Section: Introductionmentioning
confidence: 99%
“…Mouse chow contains a high concentration of folic acid, and there was no difference between young and old mothers in serum homocysteine or B12 levels or red blood cell indices (unpublished data). Maternal hyperglycemia (Priest et al, 2015), pre-pregnancy diabetes (Oyen et al, 2016) and obesity (Cedergren and Kallen, 2003; Gilboa et al, 2010; Madsen et al, 2013) are difficult to disentangle from aging in epidemiologic studies, but easily induced by a high-fat diet in the mouse. The diet had no effect on the incidence of heart defects among the offspring of young mothers, who were markedly hyperglycemic and glucose intolerant.…”
Section: The Maternal-age Associated Risk Of Congenital Heart Diseasementioning
confidence: 99%
“…Glucose and phenylalanine are prototypical examples in which supraphysiologic maternal levels can cause cardiac malformation (Hachisuga et al, 2015; Levy et al, 2001). Interestingly, the mothers of babies who have tetralogy of Fallot have a mildly elevated level of glucose at midgestation (Priest et al, 2015). A subclinical, quantitative alteration in the concentration of a maternal molecule may not cause a heart defect but could increase risk in offspring who have a genetic predisposition.…”
Section: An Unbiased Genetic Approach To the Maternal Effects On Omentioning
confidence: 99%